Utilization of Milk Waste as a Probiotic in Drinking Water for Performance Improvement and Income Over Feed Cost of Broiler Chickens - Nindria, Marisa Wahyu; Siswoyo, Siswoyo; Wijoyo, Iman Aji (JURNAL ILMIAH PETERNAKAN TERPADU, 2025)
The increasing demand for chicken meat consumption every year drives farmers to optimize the production performance of broiler chickens. The administration of probiotics has become one solution to maximize production. Probiotics are live microorganisms that enhance digestive efficiency. Prebiotics from milk waste and kefir grain starter are used as media for probiotic production, containing bacteria such as Lactobacillus, Bacillus sp., Pediococcus, Streptococcus, and Saccharomyces. This study aims to evaluate the effectiveness of performance and income over feed cost (IOFC) from probiotic supplementation during the finisher phase of broiler chickens. The research method uses a Completely Randomized Design (CRD) with four treatments and five replications: P0 (without probiotics), P1 (3% probiotics), P2 (5% probiotics), and P3 (7% probiotics). Probiotics were administered in the broilers' drinking water from evening until morning. Statistical testing employed One Way ANOVA and Duncan's multiple range test. The results showed that the best probiotic dose was P3 (7% probiotics), with 0% mortality, an average feed consumption of 152 g/bird/day, final body weight of 2203 g/bird, average daily weight gain of 257 g/bird, an average Feed Conversion Ratio (FCR) of 1.467, and an excellent Performance Index (PI) of 354 (>351-400). The 7% probiotic dose in drinking water provided the highest IOFC, amounting to Rp. 10,263 per bird.